Nexus Between Banking Industry Indicators And Economic Growth: Evidence From Nigeria - Abdullahi Shehu, Araga; Eze, Onyekachi Richard (INTI International University, 2020)
This study was carried out to investigate the nexus between banking industry indicators and economic growth in Nigeria. The investigation based on time series data from CBN statistical bulletin (1980-2019) incorporated banking indicators such as: volume of capitalization (TBC); customer deposits (VCD); credits to private sector (CPS); interest rate (INR); non-performing loans (NPL); and volume of bank frauds (VBF) as explanatory variables against GDP which proxy economic growth. The findings of the study revealed that: within the period under study: Volume of Customer Deposit (VCD) and credit to private sector (CPS) has positive and significant impact on economic growth in Nigeria while interest rate (INR); non-performing loans (NPL); and volume of bank frauds (VBF) has negative and significant impact on economic growth in Nigeria. The major recommendation is that operations of banking industry should be strengthened through appropriate policy measures towards enhancing its contribution to economic growth and development in the country. And that there should be more monitoring of banking industry indicators especially interest rate (INR); non-performing loans (NPL); and volume of bank frauds (VBF) so as to contribute positively to the growth of Nigerian economy.